1997
DOI: 10.1037/0097-7403.23.2.211
|View full text |Cite
|
Sign up to set email alerts
|

Adjusting to changes in the time of reinforcement: Peak interval transitions in rats.

Abstract: Thirty rats received training on a peak-interval procedure, where a baseline with a 20-s time of reinforcement was interspersed among cyclic transitions to other reinforcement time values (10, 20, 30, or 40 s), each of which was either in force for only a single session or for 3 sessions. Peak times were close to the time of reinforcement on the 20-s baseline and tracked the new reinforcement times both closely (but not exactly) and very rapidly. Peak time during transitions was affected by the criterion value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0
4

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 35 publications
(99 reference statements)
3
38
0
4
Order By: Relevance
“…The peak procedure is a time-discrimination procedure, which resembles a discrete-trials fixed-interval schedule with catch trials; it has been used to study the timing abilities of animals (37). Several studies have shown that old rats have deficits in time perception (57)(58)(59)(60)(61). One advantage of the peak procedure is that it allows for comparison of performance by using different types of signals and sensory modalities.…”
Section: Discussionmentioning
confidence: 99%
“…The peak procedure is a time-discrimination procedure, which resembles a discrete-trials fixed-interval schedule with catch trials; it has been used to study the timing abilities of animals (37). Several studies have shown that old rats have deficits in time perception (57)(58)(59)(60)(61). One advantage of the peak procedure is that it allows for comparison of performance by using different types of signals and sensory modalities.…”
Section: Discussionmentioning
confidence: 99%
“…A separate series of experiments in the temporal-control tradition, beginning in the late 1980s, studied the real-time dynamics of interval timing (e.g., Higa et al 1991, Lejeune et al 1997, Wynne & Staddon 1988; see Staddon 2001a for a review). These experiments have led to a simple empirical principle that may have wide application.…”
Section: Temporal Dynamics: Linear Waitingmentioning
confidence: 99%
“…Some analyses of the acquisition of a temporal discrimination have focused on the dynamics of initial acquisition (Ferster & Skinner, 1957;Kirkpatrick & Church, 2000a;Machado & Cevik, 1998). Other analyses have focused on transition effects-changes in the performance produced by changes in the fixed interval (Higa, 1997;Higa, Thaw, & Staddon, 1993;Lejeune, Ferrara, Simons, & Wearden, 1997;Meck, Komeily-Zadeh, & Church, 1984). The analysis of initial acquisition has not been integrated with the analysis of transition effects.…”
mentioning
confidence: 99%